The dynamic nature of parenting practices: a qualitative enquiry of parenting adolescents during COVID-19 - Babu, Nandita; Fatima, Mehreen; Arora, Manushi (Frontiers in Psychology, 2024)
Introduction Parenting practices are known to be dynamic, evolving in response to various factors such as societal changes, cultural norms, and individual circumstances. Understanding the dynamic nature of parenting is essential for comprehending its influence on children’s development. This study aimed to explore the adaptive nature of parenting practices amidst the backdrop of the COVID-19 pandemic, a global event that provided a unique context for examining these dynamics. Methods In-depth semi-structured qualitative interviews were conducted with six heterogeneous couples who were parenting at least one adolescent during the pandemic. Attride-Sterling’s thematic network analysis was employed to analyze the interview data. Results Five global themes emerged from the data, namely, change in parenting style due to stressors, paternal versus maternal style of parenting, intergenerational transmission of parenting practices, child-centric parenting practices, positive parenting practices and evolving parent–child relationship during COVID-19. Discussion The findings highlight the tendency of parents to adapt their parenting styles to meet the evolving needs of their children. Understanding these dynamics is crucial for supporting families during times of crisis. Future research should explore the long-term effects of these changes and effective strategies for promoting positive parent-child relationships.